2021
DOI: 10.1111/jfd.13544
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas veronii virulence and adhesion attenuation mediated by the gene aodp

Abstract: Aeromonas veronii (A. veronii) is an opportunistic pathogen of fish–human–livestock, which poses a threat to the development of aquaculture. Based on our previous studies on proteomics and genomics, we found out that the aodp gene may be related to the virulence of A. veronii TH0426. However, aodp gene encodes a hypothetical protein with an unknown function, and its role in A. veronii TH0426 is not clear. Here, we first constructed a mutant strain (△‐aodp) to investigate the functional role of aodp in A. veron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, few studies have shown that it is related to the occurrence of cow mastitis. In addition, Aeromonas_veronii can reduce nitrate to nitrite and change the metabolites in milk [62,63]. In addition, the relative abundance of microorganisms in the milk of group M was between group H and group L. Meanwhile, according to t-test results, the relative abundance of Lachnospira, Akkermansia, and Ruminococcus in group L was significantly higher than that in group M. These bacteria are recognized as beneficial bacteria.…”
Section: Discussionmentioning
confidence: 92%
“…However, few studies have shown that it is related to the occurrence of cow mastitis. In addition, Aeromonas_veronii can reduce nitrate to nitrite and change the metabolites in milk [62,63]. In addition, the relative abundance of microorganisms in the milk of group M was between group H and group L. Meanwhile, according to t-test results, the relative abundance of Lachnospira, Akkermansia, and Ruminococcus in group L was significantly higher than that in group M. These bacteria are recognized as beneficial bacteria.…”
Section: Discussionmentioning
confidence: 92%
“…Have been implicated in other functions, such as phage binding, DNA transfer, biofilm formation, cell aggregation, host cell invasion, and twitching motility Garg et al ( 2023 ) Non-filamentous Adhesins Outer membrane proteins/porins Promote binding of the bacteria to carbohydrate-rich surfaces like erythrocytes and intestinal human cells Ebanks et al ( 2005 ) Secretion systems/effectors T3SS Structural components that result in effector secretion A complex bacterial machine that transports small proteins directly from the bacterial cytoplasm across the inner and outer bacterial membrane to the extracellular environment or directly into the target host cell Pillai ( 2006 ) aexT/aexU T3SS effector protein A T3SS effector, homologous to the P . aeruginosa effectors ExoT/ExoS, with ADP-ribosyltransferase and GTPase activities Braun et al ( 2002 ); Burr et al ( 2003 ); Sha et al ( 2007 ) aopP and other T3SS effector proteins T3SS effector protein Interferes with host cell signaling and in other ways modifies/regulates pathogenicity Matys et al ( 2020 ); Rangel et al ( 2019 ); Zhang et al ( 2022a ) T6SS Structural Components that result in effector secretion A bacterial machine that constitutes a phage-like injectosome complex that serves to translocate effectors directly into competing bacterial cells as well as eukaryotic host cells Suarez et al ( 2008 ) hcp Hemolysin coregulated protein Surface-exposed structural components that might be released in culture supernatants or into eukaryotic cells during translocation Cai et al ( 2022 ); Tekedar et al ( 2018 ) vgrG Valine-glycine repeat protein G Acts as a conduit for T6SS effector pro...…”
Section: Quorum Sensingmentioning
confidence: 99%